2021
DOI: 10.3390/su13179956
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heuristic Priority Rules in the Solution of the Resource-Constrained Project Scheduling Problem

Abstract: Resource-constrained project scheduling (RCPS) aims to minimize project duration under limited resource availabilities. The heuristic methods that are often used to solve the RCPS problem make use of different priority rules. The comparative merits of different priority rules have not been discussed in the literature in sufficient detail. This study is a response to this research gap. It compares 17 heuristic priority rules and seeks the best performing heuristic priority rule. This is the first study ever tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We have no real explanation for this observation, but we saw that when we applied both SGSs on the test data, 33% of the time, the SSGS performed best, and in 47% of the cases, the PSGS performed best (in 20% of the cases, the results were identical). Some studies show that no method outperforms the other (Kolisch and Hartmann [12], Kolisch [65]), while other studies have shown that the PSGS scheme outperforms the SSGS (Türkakın et al [67], Coelho and Vanhoucke [71]). None of them give reasons why this is the case.…”
Section: The Performance Of Small-sized Project and Single Sgsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have no real explanation for this observation, but we saw that when we applied both SGSs on the test data, 33% of the time, the SSGS performed best, and in 47% of the cases, the PSGS performed best (in 20% of the cases, the results were identical). Some studies show that no method outperforms the other (Kolisch and Hartmann [12], Kolisch [65]), while other studies have shown that the PSGS scheme outperforms the SSGS (Türkakın et al [67], Coelho and Vanhoucke [71]). None of them give reasons why this is the case.…”
Section: The Performance Of Small-sized Project and Single Sgsmentioning
confidence: 99%
“…Thus, the performance can be better revealed. In a more recent study [67], which results are based on the performance of 17 priority rules, the authors have shown that the parallel SGS is slightly superior to the serial in most cases. Therefore, there is no guideline for which scheme is more effective than the other to be used in the training phase.…”
Section: Single Modelsmentioning
confidence: 99%